Singing nation and politics: music and the" decade of crisis" in Zimbabwe, 2000-2010 - Muwati, Itai; Charamba, Tyanai; Tembo, Charles (Midlands State University Press, 2022)
Singing Nation and Politics: Music and the "decade of Crisis" in Zimbabwe, 2000-2010